EL SILENCIO DE LAS VÍCTIMAS DE ABUSO EN ENTORNO ECLESIAL. ANÁLISIS A PARTIR DEL CASO PERUANO - (:unkn) unknown (Universidad Pontificia Comillas, 2024)
Unlike what happens in other countries, in Peru, except for the Sodalitium case, almost no victim of abuse of conscience and sexual, in ecclesial settings, has publicly denounced the facts. This article aims to analyze the reasons for this silence. To th...
Keywords: Abuso eclesial; Víctimas